English-Indonesian Translation Strategies in Children's Songs - Baihaqi, Tiffani Rizki Putri; Subiyanto, Agus (Development in Language Studies, 2022)
Producing a singable translated song, meaning that the words fit the melody, is far from easy because it involves not only syllables, rhymes, and melody of the original song, but also the distinct cultures from both the Source Text (ST) and the Target Text (TT). Through bilingual songs, children can learn their second language more easily and in a fun way. This research aims to discover the strategy of children’s songs translation from English to Indonesian so that they are acceptable, singable, and most importantly, they convey the same messages. Four English children’s songs along with their Indonesian version of the same titles were analysed using descriptive qualitative methods, with random sampling, by juxtaposing and scrutinizing the lines to find out whether or not there are omissions, additions, and paraphrases in the translation process on the ST and TT. The results showed that there are omissions, additions, and paraphrases in translating those eight children’s songs. Despite having different research objects, the results were similar to the previous research, thus supporting the theories and findings of those research.